A corpus-based multimodal approach to the translation of restaurant menus. (2nd January 2019) - Li, Saihong
ABSTRACT: Translated restaurant menus facilitate tourism and consumerism, but menu translation remains a peripheral area of professional translation and translation studies. This has economic consequences, because translations that exclude a dish's ingredients, cooking methods, or cultural associations may deter consumers. This article analyses translated menus featuring Chinese dishes in order to establish the extent to which intersemiotic, image-based approaches are used to complement written translations; the level of consistency with which ingredients and cooking methods are translated; and the frequency of culturally specific dish names that are challenging to translate. A corpus-based methodology is used to compare 3, 000 Chinese dish names and their translations from China, Taiwan and abroad. The data reveals very limited intersemiotic translation in existing menus, inconsistent translations of ingredients and cooking methods, and a high percentage of dishes with culturally specific names. However, these are often omitted in translation, or lack supplementary information concerning their ingredients. It is proposed that a multimodal translation approach incorporating Jakobson's tripartite theory can enhance menu translation. Menus featuring Pinyin as an intralingual translation can engage learners of Chinese who use this method; interlingual explicitation clarifies a dish's ingredients, cooking methods and cultural specificity; and intersemiotic, image-based translation conveys culinary artistry clearly.